Nordycka koncepcja rozwoju miast, czyli o zarządzaniu przestrzenią miejską na przykładzie Finlandii, Szwecji i Islandii - Banaś, Monika (Studia Etnologiczne i Antropologiczne, 2010)
The article deals with the issue of creating and managing the urban space in Nordic countries. On the basis of three countries of the Nordic area, three conceptions of urbanist arrangement, assuming the satisfaction of the needs of a contemporary inhabitant, as well as the one who will appear here within the period of next 10—15 years were presented. The experiences of Finnish, Swedish and Icelandic urbanists serve as a demonstration of deep in thought and thoroughly planned actions modeling the shape and functioning of cities. Although the Nordic urban space development conceptions, taking into account a different geographical and historio cultural context, are different for each of the countries, they have a few features in common. The first of them is a futuristic perspective without neglecting the present day needs. The second consists in the care of the environment, revealing itself in the endeavours to inscribe the city into the natural environment. The third one, on the other hand, boils down to the care of the psycho physical hygiene of the inhabitants. Particular country variants contribute to a joint Nordic model of arranging the urban space, look¬ing after and watching over its appropriate development. The Nordic model of city development and urban tissue creation, in its national variants, creates a specific philosophy of the city, and different to such an extent that it visibly stands out from the patterns of the continental Europe.